I’m translating – Am I writing? On Translating Self-referential Poems - Waligóra, Agnieszka (Porównania, 2020)
The article describes an attempt to conduct an experimental translation of a self-referential poems with the conversion of the subjective “I who write” into the subjective “I who translate”. It contains numerous translations of three poems (written by Robert Lowell, Frank O’Hara and Jane Kenyon). They are interpreted and compared with the original works and provided with commentary, which situates them in a broader translatological and theoretical context. The translations were made by the students of the translation speciality (Wydział Filologii Polskiej i Klasycznej, Adam Mickieiwcz Univeristy in Poznań).